Correlation of circulating diabetes markers with elevated serum antithyroglobulin antibodies in type 2 diabetes patients - Batool Ibrahim Aljasmmi; Awadh S Alsubhi; Abdulrahman Algarni; Elryah I Ali; Ammar Abdelmola; Hussam Ali Osman; Abdelrahman Mohamed Ahmed Abukanna; Marwan Ismail; Asaad Babker; Salah Eldin Omar Hussein (Italian Journal of Medicine)
A total of 250 males and females were recruited to participate in this cross-sectional and case-control study that aimed at measuring several biomarkers [fasting blood glucose (FBG), glycated hemoglobin (HbA1c), thyroid hormonal profile, and antithyroglobulin antibody (ATG)] in diabetic and non-diabetic patients and comparing circulating markers of diabetes mellitus with elevated serum ATG levels in type II diabetes patients who used various analyzers. The assays were performed on Roche COBAS C311, COBAS e 411/601, and Beckman Coulter (DXC 700 AU) analyzers. The mean and standard deviation were calculated, and the independent t-test and one-way analysis of variance were used for comparison. Linear regression was conducted to assess correlations. A p-value of <0.05 was considered statistically significant. This study included 125 diabetic patients compared with 125 healthy males and females, with ages ranging from 20 to 81 years and a duration of diabetes mellitus between 4 to 15 years. The results demonstrated a significant difference in FBG, HbA1c, thyroid-stimulating hormone (TSH), free triiodothyronine (FT3), free thyroxine (FT4), and ATG levels between the diabetic patients and the healthy individuals, compared to age, gender, and duration of the disease. A moderate positive correlation was observed between FBG and HbA1c, as well as between FT3 and FT4; a negative correlation was found between FBG and HbA1c levels and TSH levels. A significant positive correlation between ATG and serum TSH levels observed in patients with type 2 diabetes mellitus indicated a strong relationship between thyroid dysfunction and diabetes, compared to the age and duration of the disease.